Interfaith Communication in Digital Space: A Phenomenological Study Experience Interfaith Communication among Indonesian Users on the App Hellotalk - Firmansyah, Bayu; Samsudin, Ahmad (Interdisciplinary Journal of Advanced Research and Innovation, 2026)
This study investigates the phenomenon of interfaith communication among Indonesian Muslim users of the HelloTalk language-exchange application, examining how this platform has evolved into a hybrid space of “Digital Religion”. Employing Alfred Schutz’s social phenomenology and Abraham Maslow’s hierarchy of needs as complementary theoretical frameworks, this qualitative research utilized purposive sampling to select two key informants who actively engage in interfaith discussions on HelloTalk. Data were collected through semi-structured in-depth interviews conducted online and analyzed using phenomenological reduction. Trustworthiness was ensured through source triangulation and member checking. The novelty of this study lies in its dual-framework approach  simultaneously mapping motivational structures (Schutz) and psychological needs (Maslow) within a non-religious digital platform. The results indicate that users’ Because Motives are rooted in past positive experiences with non-Muslims and inspiration from the Prophet’s da’wah stories. Meanwhile, the In-Order-To Motives are dominated by a missionary mission to earn spiritual merit (Self-Transcendence), a desire to correct global misconceptions about Islam (Esteem and Safety Needs), and the aspiration to forge cross-cultural global connections (Love/Belonging and Esteem). The findings demonstrate that HelloTalk users deliberately sacralize a secular digital platform, transforming it into a field of spiritual service. This study contributes theoretically to Digital Religion scholarship by documenting a novel form of faith diplomacy enacted by lay Muslim users through algorithm-mediated intercultural communication, and contributes practically by informing digital da’wah strategy and interfaith dialogue programs in the Indonesian Muslim context.